2011
DOI: 10.1159/000329863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Incidence of Endophthalmitis after Intravitreal Injection of Anti-Vascular Endothelial Growth Factor

Abstract: Aims: To report the incidence of infectious and noninfectious endophthalmitis after intravitreal injection of anti-vascular endothelial growth factor (VEGF) from a multicenter clinical trial in Japan. Methods: A retrospective multicenter review of the data of patients who received intravitreal anti-VEGF injections between January 2007 and March 2011 was undertaken. Cases with the clinical diagnosis of endophthalmitis resulting from intravitreal injection were identified and reviewed. Results: A total of 5,236 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 65 publications
0
27
0
5
Order By: Relevance
“…Furthermore, we reported that bevacizumab injection was significantly higher to cause endophthalmitis compared with ranibizumab. 25 To realize an appropriate costeffectiveness treatment for AMD is needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reported that bevacizumab injection was significantly higher to cause endophthalmitis compared with ranibizumab. 25 To realize an appropriate costeffectiveness treatment for AMD is needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…28 The incidence rate found in this study of 0.025% of PIAE is comparable to previous work that has quoted rates ranging from 0.02-0.1%. 9,10,12,[14][15][16][17][18]21,22 This is the largest prospective study to ascertain an incidence rate for PIAE in the UK population when intravitreal anti-VEGF is used to treat exudative ARMD.…”
Section: Incidence Ratementioning
confidence: 99%
“…This rate is comparable to or better than other studies of endophthalmitis following intravitreal therapy and cataract surgery. 15,17,18,21,32,33,[35][36][37] As with endophthalmitis following cataract surgery, vitreous sampling achieved a higher organism yield rate compared with aqueous sampling. 28,32,33 However, as aqueous sampling yielded an organism that was not identified by vitreous sampling in two cases, it may be optimal to perform both vitreous and aqueous sampling in the event of PIAE in order to maximise the chance of identifying a causative pathogen.…”
Section: Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In einer retrospektiven 6-Jahres-Analyse berichtet Moshfeghi et al von 12 Patienten mit einer Endophthalmitis von 60 322 behandelten Augen, was einer Inzidenz von 0,02 % entspricht [17]. Eine irische Studie berichtet von einer Inzidenz von 0,1 % bei 5900 Injektionen und eine japanische Arbeit berichtet von einer Inzidenz von 0,095 % bei 5236 behandelten Augen [18,19].…”
unclassified